Isolasi dan Identifikasi Senyawa Flavonoid dalam Fraksi n-Butanol Daun Dewa (Gynura pseudochina (L.) DC) secara Spektrofotometri UV-Cahaya Tampak - RATNA DJAMIL; CATHARINA YENNI (Fakultas Farmasi Universitas Pancasila, 2014)
Plant of dewa leaves (Gynura pseudochina ( L. ) DC) from family Asteraceae is a plant that has been widely used for some treatments including blood circulation , trauma, bleeding and blood clot. In this research, the isolation and identification of flavonoid compounds in n-butanol fraction of the methanol extract of dewa leaves (Gynura pseudochina ( L. ) DC) has been carried out. The compound in Dewa leaves was isolated using maceration with methanol which was then partitioned by n-hexane solvent, ethyl acetate and n-butanol. The n-butanol phase was then isolated by paper chromatography with BAW (4:1:5) as a mobile phase which resulted in seven bands. Each of the bands was further identified using spectrophotometry UV-vis to show wavelength of maximum absorption that was given from only three bands for flavonoids namely NB-III, NB-V and NB-VI. Moreover, the bands were further eluated with 15% acetic acid as second mobile phase and the spot appeared in the presence of ammonia. The final isolates were identified by UV-vis spectrophotometer with addition of a shift reagent. The resulting spectrum from the isolates NB-III was considered as the one of flavonol compounds with the OH group at theposition of 3.7 and oxygenation at 6 or 8 and o– at OH group in ring B; NB-V isolates, OH groups at positions 3, 5, 7 and o– at OH group in ring B and NB-VI isolates, the OH group at position 5,7 and 8.